2019
DOI: 10.1108/jaee-01-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of audit committee independence, board ethnicity and family ownership on earnings management in Malaysia

Abstract: Purpose The purpose of this paper is to investigate the effect of audit committee independence, board ethnicity and family ownership on earnings management in Malaysia. Design/methodology/approach The effect of audit committee independence, board ethnicity and family ownership on corporate governance is investigated via 1,206 firm-year observations between the fiscal years of 2004 and 2009 of Bursa Malaysia listed firms. Panel data regression analysis is used to analyze the relationship. Findings The findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 97 publications
5
28
0
4
Order By: Relevance
“…In the additional analyses, the results remain the same at different percentages of family ownership concentration, using individual REM measurement and alternative regression estimation. The findings are in line with the results of recent studies that provide evidence for the positive role of family ownership in reducing EM and producing high-quality financial reporting (Achleitner et al, 2014;Boonlert-U-Thai & Sen, 2019;Hashmi et al, 2018;Mohammad & Wasiuzzaman, 2020). However, they contradict the findings of previous studies which suggest that family firms are associated with higher REM (Eng et al, 2019;Razzaque et al, 2016).…”
Section: Introductionsupporting
confidence: 76%
“…In the additional analyses, the results remain the same at different percentages of family ownership concentration, using individual REM measurement and alternative regression estimation. The findings are in line with the results of recent studies that provide evidence for the positive role of family ownership in reducing EM and producing high-quality financial reporting (Achleitner et al, 2014;Boonlert-U-Thai & Sen, 2019;Hashmi et al, 2018;Mohammad & Wasiuzzaman, 2020). However, they contradict the findings of previous studies which suggest that family firms are associated with higher REM (Eng et al, 2019;Razzaque et al, 2016).…”
Section: Introductionsupporting
confidence: 76%
“…see Doidge et al, 2004). Alternatively, since family owners have long ownership time horizons and control their firms, the incentives for earnings management in family firms could be lower as found by Mohammad and Wasiuzzaman (2020) in their study of Malaysia.…”
Section: Introductionmentioning
confidence: 98%
“…Prior studies in Malaysia reported that REM is prevalent (Abdul Latif et al, 2016;Enomoto et al, 2015;Kalgo et al, 2019;Nasir et al, 2018;Rahmat et al, 2020;Salleh, 2009). They extensively investigated the effect of corporate governance characteristics on EM practices and the findings show inconsistent results (Al-Rassas and Kamardin, 2016;Mohammad et al, 2016;Mohammad and Wasiuzzaman, 2020), suggesting that governance monitoring in Malaysian companies is currently inadequate in mitigating EM (Mohammad Investment in outside governance monitoring et al, 2016). This could be because companies comply with the corporate governance regulations only by establishing symbolic governance mechanisms (Abdul Latiff and Taib, 2011;Abdullah, 2006), which might be ineffective (Abdullah, 2006;Mohammad et al, 2016).…”
Section: Introductionmentioning
confidence: 99%